EFISIENSI TEKNIS USAHATANI JAGUNG MANIS DI DESA GUNUNG MALANG KECAMATAN TENJOLAYA KABUPATEN BOGOR: PENDEKATAN DATA ENVELOPMENT ANALYSIS - Amandasari, Melissa; Nurmalina, Rita; Rifin, Amzul (Forum Agribisnis, 2014)
Efficiency can be used as a measurement for decision making. Technical efficiency is one of them. The objectives of the research are (1) to analyze farming techniques and input usage, (2) to measure the technical efficiency and (3) to identify factors affecting technical efficiency of maize farm in Gunung Malang, Tenjolaya, Bogor Regency. Data Envelopment Analysis (DEA) approach and Tobit Regression are used to analyze. The result shows that farmers in Gunung Malang are inefficient in the use of production inputs. Farmers need to decrease manure usage, TSP fertilizer, and outside labor for technical efficiency. Factors that are affecting the technical efficiency are formal education level, number of household member and farmer association membership.